ANALISIS RASIO PROFITABILITAS DAN SOLVABILITAS DALAM MENGUKUR KINERJA KEUANGAN PADA PT BANK KB INDONESIA TBK - Sitio, Demfi Margaretha; Tampubolon, Dealova; Panggabean, Maya Sabirina (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the financial performance of PT Bank KB Indonesia Tbk for the period 2020-2024 using profitability ratios such as Net Profit Margin, Return on Assets, and Return on Equity, as well as solvency ratios including Debt to Assets Ratio and Debt to Equity Ratio. A quantitative descriptive method is employed, using data from the bank's annual financial statements published on the Indonesia Stock Exchange and the company's official website. Each financial ratio is calculated and its development is observed over the years. The results indicate that the company has a fairly strong ability to generate profits, as evidenced by the relatively high NPM and ROE values. However, the ROA value is lower, which indicates that the company has not fully utilized the assets it owns to generate profits. Although there has been an improvement in the company's solvency in recent years, the company is still heavily dependent on debt. Overall, the company has a good ability to generate profits; however, to make its finances healthier, more stable, and sustainable in the future, it still needs to improve the effectiveness of asset usage and manage debt better.